2009
DOI: 10.1210/en.2008-1162
|View full text |Cite
|
Sign up to set email alerts
|

Coingestion of Acylglycerols Differentially Affects Glucose-Induced Insulin Secretion via Glucose-Dependent Insulinotropic Polypeptide in C57BL/6J Mice

Abstract: The precise role of fat in postprandial glycemia and insulinemia has not been thoroughly researched because postprandial blood glucose and concurrent insulin secretion are largely assumed to be proportional to carbohydrate intake. Recent studies have suggested that dietary fat differentially regulates the postprandial insulin response. To explore this, we examined the effects of coadministered fat on glucose-induced glycemia and insulinemia in C57BL/6J mice. The insulin response to glucose was augmented by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 62 publications
4
34
0
Order By: Relevance
“…More recently, we have shown that 1,3-DAG-rich oil stimulates less GIP secretion compared with TAG-rich oil of a similar fatty acid composition (35), supporting the lower postprandial insulin response after 1,3-DAG-rich oil ingestion in combination with carbohydrate. There is strong evidence for its anabolic characteristics and role in the regulation of adipogenesis of GIP (14).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…More recently, we have shown that 1,3-DAG-rich oil stimulates less GIP secretion compared with TAG-rich oil of a similar fatty acid composition (35), supporting the lower postprandial insulin response after 1,3-DAG-rich oil ingestion in combination with carbohydrate. There is strong evidence for its anabolic characteristics and role in the regulation of adipogenesis of GIP (14).…”
supporting
confidence: 64%
“…Since very little is known about the apparent mechanism of fat-stimulated GIP secretion, we hypothesized that fat-induced GIP secretion may be triggered by intestinal fatty acid transport. Previous studies indicated that fat-stimulated GIP secretion was associated with chylomicron formation (26,35). Either chylomicron formation (24) or fatty acid uptake (23) was shown to be mediated by fatty acid translocase (FAT)/CD36 in the proximal intestine.…”
mentioning
confidence: 99%
“…Seminal studies performed by Han et al [11] demonstrated that WB increases the expression of proteins related to fatty acid oxidation by modulating the sterol-regulatory element binding protein pathway, and increases lipolysis and browning of adipocytes [12] in mice. On the other hand, many studies have demonstrated that chronic disruption and suppression of GIP signaling, either genetically, or by vaccination against GIP, or by administration of materials that reduce postprandial blood GIP, leads to high fat utilization and accelerates lipolysis in adipose tissue [2125,2729,34]. The findings of the present study are consistent with previous findings, and add new insight into the anti-obesity mechanisms of WB.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, intravenous administration of GIP to healthy lean men lowers resting energy expenditure (REE) [26]. In our previous study, we found that the dietary components that control GIP secretion, such as diacylglycerol [27], 1-monoolein [28], and RS4-type-resistant starch [29], increase postprandial fat utilization and prevent high-fat diet-induced obesity in mice. Reduction of postprandial GIP secretion can increase postprandial energy catabolism and prevent obesity.…”
Section: Introductionmentioning
confidence: 99%
“…These include contributions from fatty acid transporter, member 4 (74), activation of atypical PKCζ (75), and indirect stimulation by chylomicrons and other lipoproteins released by neighboring enterocytes. In support of the latter hypothesis, administration of the hydrophobic surfactant and inhibitor of intestinal chylomicron formation Pluronic L-81 (76) led to reduced lipidinduced GIP secretion in mice (77) and rats (78), and in I cells, the regulation of CCK release by fatty acids was lipoprotein dependent and was attributed to activation of immunoglobulin-like domain containing receptor 1 (79). Mice lacking monoacylglycerol acyltransferase 2 or diacylglycerol acyltransferase 1 (DGAT1), enzymes that sequentially resynthesize triglycerides to be incorporated into chylomicrons, also exhibited impaired GIP release in response to an oral triglyceride load.…”
Section: Gut Microbiota Host Defense and Eec Signalingmentioning
confidence: 85%